Presupposition in Meme Comments on a Video Post in Instagram (Pragmatic Analysis) (Sastra Inggris UNPAM, 2025)
This study examines the use of presuppositions in Instagram comments, applying Yule’s (1996) theory to explore how presuppositions shape online interactions. Presuppositions, which rely on shared knowledge, facilitate efficient communication by indirectly implying truths. The study employs a descriptive qualitative approach to identify presuppositions and classify their types. Key findings suggest that existential presupposition is the most common, contributing to brevity, engagement, and emphasis. Case studies from the @savagecomedy account illustrate how presuppositions enhance information that is not explicitly stated within a given context. This research highlights the evolving role of language in digital spaces and suggests further investigation into presupposition strategies across social media platforms.